Analysis of Pink Tourism From A Queer Criminology Perspective: The Dynamics of Perception and Stigma Experienced By Transpuan In Jakarta - Vion Patrick Putra Luwansa; Nadia Utami Larasati (International Journal of Science and Environment (IJSE), 2026)
Jakarta's rapid growth as an urban tourism hub has coincided with its quiet integration into the global "pink tourism" network, a market segment oriented toward LGBTQ+ travelers. Yet this integration unfolds inside a society still governed by strong heteronormative and religious norms, creating a persistent tension between economic openness and social exclusion. This study examines how public perception, social norms, and mechanisms of social control shape the lived experience of transpuan (trans women) who are visible participants in Jakarta's entertainment and tourism spaces. Using a qualitative descriptive design and data triangulation across in-depth interviews with five purposively selected informants, literature review, and documentary analysis, the study applies the interactive analysis model of data condensation, display, and conclusion drawing. Findings show that stigma toward transpuan operates in a layered and sector-specific manner: tourism-industry actors tend to accept transpuan on economic and functional grounds, while the wider community extends only conditional tolerance rooted in religious and moral narratives, and state institutions maintain formally non-discriminatory administrative access while tolerating informal, identity-based enforcement. Read through a Queer Criminology lens, these patterns reveal a form of symbolic criminalization in which transpuan identity itself, rather than any proven unlawful act, becomes sufficient grounds for surveillance, restriction, and exclusion. The study also documents transpuan agency and resilience through advocacy, digital adaptation, and participation in the tourism economy. The research contributes to Indonesian criminology by repositioning transpuan as legitimate subjects of analysis and offers practical implications for inclusive tourism policy in Jakarta.